ABBA+BraiAn, an integrated suite for whole-brain mapping, reveals brain-wide differences in immediate-early genes induction upon learning - Nicolas Chiaruttini; Carlo Castoldi; Linda Maria Requie; Carmen Camarena-Delgado; Beatrice Dal Bianco; Johannes Gräff; Arne Seitz; Bianca A. Silva (Cell Reports)
Summary: Unbiased characterization of whole-brain cytoarchitecture is crucial for understanding brain function, requiring precise mapping of 2D histological sections onto 3D brain atlases. We introduce two software tools to facilitate this process: Aligning Big Brains and Atlases (ABBA), designed to streamline the precise and efficient registration of 2D sections to 3D reference atlases, and BraiAn, an integrated suite for multi-marker automated segmentation, whole-brain statistical analysis, and data visualization. Combining these tools, we conducted a comprehensive comparative study of the whole-brain expression of three widely used immediate-early genes (IEGs)—cFos, Arc, and NPAS4—across three memory-related behavioral conditions. Our findings reveal significant differences in their distribution and induction patterns, suggesting that these IEGs offer complementary, rather than equivalent, information about neural activity across brain regions and activity states.